25 Years of PI5P - Rameh, Lucia E.; Blind, Raymond D. (Frontiers in Cell and Developmental Biology, 2023)
The accidental discovery of PI5P (phosphatidylinositol-5-phosphate) was published 25 years ago, when PIP5K type II (phosphoinositide-4-phosphate 5-kinase) was shown to actually be a 4-kinase that uses PI5P as a substrate to generate PI(4,5)P2. Consequently, PIP5K type II was renamed to PI5P4K, or PIP4K for short, and PI5P became the last of the 7 signaling phosphoinositides to be discovered. Much of what we know about PI5P comes from genetic studies of PIP4K, as the pathways for PI5P synthesis, the downstream targets of PI5P and how PI5P affects cellular function all remain largely enigmatic. Nevertheless, PI5P and PI5P-dependent PI(4,5)P2 synthesis have been clearly implicated in metabolic homeostasis and in diseases such as cancer. Here, we review the past 25 years of PI5P research, with particular emphasis on the impact this small signaling lipid has on human health.